An increase in the concentration of abscisic acid is critical for nitric oxide-mediated plant adaptive responses to UV-B irradiation - Tossi, Vanesa (2009)
• Here, the link between UV-B stimulus and the abscisic acid (ABA)-induced nitric oxide (NO) synthesis pathway was studied in leaves of maize (Zea mays). • The ABA concentration increased by 100% in UV-B irradiated leaves. Leaves of viviparous 14 (vp14), a mutant defective in ABA synthesis, were more sensitive to UV-B-induced damage than those of the wild type (wt). ABA supplementation attenuated UV-B-induced damage in both the wt and vp14. The hydrogen peroxide (H2O2) concentration increased in the irradiated wt, but changed only slightly in vp14. This increase was prevented by diphenylene iodonium (DPI), an inhibitor of NADPH oxidase (pNOX). • NO was detected using the fluorophore 4,5-diamino-fluorescein diacetate (DAF-2DA). DAF-2DA fluorescence increased twofold in UV-B-irradiated wt leaves but not in vp14 leaves. H2O2 and NO production was restored in vp14 plants supplied with 100 μM ABA. Catalase, DPI and the NO synthase (NOS) inhibitor NG-nitro-L-arginine methyl ester (L-NAME) partially blocked UV-B-induced NO accumulation, suggesting that H2O2 as well as NOS-like activity is required for a full plant response to UV-B. NO protects against UV-B-induced cell damage. • Our results suggest that UV-B perception triggers an increase in ABA concentration, which activates pNOX and H2O2 generation, and that an NOS-like-dependent mechanism increases NO production to maintain cell homeostasis and attenuate UV-B-derived cell damage. © The Authors (2009).